Gaharu dan Potensinya dalam Pengembangan Ekowisata di Nusa Tenggara Barat - Robert Siburian (Fakultas Pertanian Universitas Mataram, 2020)
Agarwood is a fragrant non-wood product. West Nusa Tenggara is a site for growing agarwood tree. In the world, especially in the Middle East, the Arabian people are the most consumptive to agarwood. For demand to agarwood is high but the agarwood in forest is rarely, making the price of agarwood in the market is expensive. Agarwood farmers in West Nusa Tenggara could not be able to supply the demand because agarwood product from natural forest is very little. In answering the high demand to natural agarwood, the farmers develop agarwood cultivation. Agarwood trees were planted in theirs yards and gardens, and after some years the agarwood trees inoculated with inoculation as a way to get aromatic resin. Developing agarwood plantation of farmer can become a potential tourism destination in West Nusa Tenggara to add pre-existing tourist attraction. Through this paper, I would like to explain why agarwood plantation and all activities following it become a potential tourism attraction which will improve welfare of agarwood farmers in West Nusa Tenggara, especially in Lombok Island.